Dance steps, dynamic elements with rotation and throw and mastery elements in rhythmic gymnastics routines - Batista, A.; Garganta, R.; Avila-Carvalho, L (Science of Gymnastics Journal, 2017)
Analyze of individual elite routines allows to gain more knowledge about the performance of the RG structure. Therefore, the aim of this study is to know the difficulty elements diversity (dance steps, masteries and dynamic elements with rotation and throw) in individual routines of elite gymnasts who competed at the 2013 and 2014 Lisbon RG World Cup and to compare these characteristics across different ranking groups. 288 official difficulty forms of 4 routines were analyzed. The gymnasts` routines were clustered into three groups according to their ranking position. Non-parametric Kruskal-Wallis and Mann-Whitney tests were used. Pearson Correlation was used to analyze the association degree of the difficulty elements in the gymnasts` final score. The best gymnasts presented routines with some different characteristics, however, we verified a high similarity in the difficulties elements analyzed in the compositions that can compromise the originality and variety of this sport. We observed that the higher gymnasts` final score, have also higher departure difficulty score; lower number of combinations of base and criteria in masteries; higher number of non-fundamental and lower number of fundamental group elements in masteries. On the other hand, higher number of masteries and number of additional criteria of body rotations in dynamic elements with rotation and throw, lower the gymnasts` final score. However, we believe that the real differences in the ranking groups is mostly justified by evaluation of the judges of the difficulty elements presented in the official Difficulty forms and in the execution quality of the gymnasts.